RELEVANSI IDE THE OPEN SOCIETY KARL POPPER DAN MULTIKULTURALISME DALAM PEMBELAJARAN SEJARAH - Azril Azifambayunasti (Universitas Negeri Malang, 2022)
The Open Society by Karl Popper is an idea that opposes any kind of oppression and to-talitarianism, so that what is called an open society will be realized, a society that priori-tizes freedom but remains in the corridor of law and ethics. The Open Society is an idea that opposes socialism and capitalism at the same time. As an important idea in the modern age, The Open Society Popper must be able to use in life, just like knowledge that has an axiological basis. This idea is also closely related to democracy which up-holds individual freedom while still being controlled by law. On the one hand, The Open Society can be implemented in the education democracy movement, which is then called multicultural education, with kind of values that accommodate the freedom and equality of individual rights in society. The purpose of this study is to discuss the idea of The Open Society and its relevance to historical education, especially regarding multiculturalism. This discussion was reviewed using the literature study method. The results of this analysis show that The Open Society Popper can be used as a basis for multicultural education because it gives high respect to individual freedom and opposes domination by certain groups, while still respecting the law.Open Society menurut Karl Popper adalah sebuah gagasan yang menentang segala bentuk penindasan dan totalitarianisme, sehingga akan terwujud apa yang disebut masyarakat terbuka, masyarakat yang mengutamakan kebebasan namun tetap dalam koridor hukum dan etika. Masyarakat Terbuka adalah sebuah ide yang menentang sosialisme dan kapitalisme pada saat yang bersamaan. Sebagai sebuah ide penting di era modern, The Open Society Popper harus dapat digunakan dalam kehidupan, seperti halnya pengetahuan yang memiliki landasan aksiologis. Gagasan ini juga erat kaitannya dengan demokrasi yang menjunjung tinggi kebebasan individu dengan tetap dikendalikan oleh hukum. Di satu sisi, Masyarakat Terbuka dapat diimplementasikan dalam gerakan demokrasi pendidikan, yang kemudian disebut pendidikan multikultural, dengan nilai-nilai yang mengakomodasi kebebasan dan persamaan hak individu dalam masyarakat. Tujuan penelitian ini adalah membahas mengenai gagasan The Open Society dan relevansinya dengan pendidikan sejarah, khususnya perihal multikulturalisme. Pembahasan ini dikaji menggunakan metode studi pustaka. Hasil analisis i menunjukkan bahwa The Open Society Popper dapat dimanfaatkan sebagai landasan pendidikan multikultural karena memberikan penghargaan yang tinggi terhadap kebebasan individu dan menentang penguasaan oleh kelompok tertentu, dengan tetap hormat pada hukum.